A comprehensive India-wide social vulnerability analysis: highlighting its influence on hydro-climatic risk. (14th January 2020) - H, Vittal; Karmakar, Subhankar; Ghosh, Subimal; Murtugudde, Raghu
Abstract: The impacts of hazard events such as extreme rainfall, heatwaves, and droughts are substantial and represent an increasing threat over India. Effective adaptations to these hazards require an in-depth understanding of their physical and socioeconomic drivers. While hazard characteristic models have been substantially improved, compelling evidence of the spatio-temporal analysis of social vulnerability (SoV) throughout India are still lacking. Here, we provide the first analysis of the SoV to disasters at a national-scale for the past two decades using a robust data envelopment analysis framework, which eliminates subjectivity associated with indicator weighting. An interesting result is that SoV has decreased over past decade, which is primarily due to an increase in literacy rate and conversion rate of marginalized groups to main working population, and a decrease in child population due to use of birth control. Contrarily, while analyzing hydro-climatic hazards over India, we notice an increase in probability of their occurrence over significantly large portions all over India, particularly in Karnataka, Maharashtra, Odisha, North-Eastern states and Telangana. The spatial pattern of increase is surprisingly similar for all three considered hazards, viz. extreme precipitation, heatwaves, and drought. Combining the information from SoV and hazard analysis, we further estimate the risk to hydro-climatic extremes. A notable observation is the synchronized increase in hazard and risk in these regions, indicating that hazards are contributing significantly to the increasing risk and not SoV. Further analyses of mortalities induced by different hazards indicate that deaths per million on a decadal-scale have either decreased or remained constant in recent decades, which suggests that mortality is decreasing despite the increasing risk of hazards over India. This also indicates an enhanced capacity for adaptation, which can be attributed to the decadal decrease in SoV observed in the present study.